DEVELOPMENT OF AN INSTRUCTIONAL PACKAGE ON CONSTRUCTION MATERIALS BY USING BOARD GAMES AND THE MIAP LEARNING PROCESS TO ENHANCE STUDENTS’ ACHIEVEMENTS - Phetjan, Peerapong; Buaklay, Nannam; Sumim, Suebsak; Oungthong, Metha (Journal of Industrial Education, 2023)
This research has developed an instructional package on construction materials using a board game and the MIAP learning process to enhance student achievement. This study is experimental research. The population consisted of 570 students in their second year at a vocational institution. They were randomly selected for use the study via cluster random sampling. Each of two sample groups consisted of 30 individuals. The first group, a control group, consisted of students who learner using conventional methods. The second group, an experimental group, that learns through a researcher – created instructional package. The research instruments included 1) lesson plans, 2) a board game on constructional materials, 3) a questionnaire on an instructional package, and 4) a four–option multiple-choice test for assessing learning achievement in construction materials. Thirty items had an IOC between 0.25 and 0.50, and a reliability of 0.63. Data analysis utilized the mean, standard deviation, and t-test, as a consequence of the development of the instructional package for construction materials consisted of seven sections, which received the highest rating in expert evaluation. The comparison of learning achievement between the control group and the experimental group revealed that the learning achievement of the experimental group students was significantly higher than that of the control group at the .05 level.